2006
DOI: 10.1080/09297040600681315
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of the CVLT-C in Pediatric Epilepsy

Abstract: The current study used archival data to evaluate the fit of six latent variable models, originally generated by Donders (1999), for the California Verbal Learning Test-Children's Version (CVLT-C; Delis, Kramer, Kaplan, & Ober, 1994) in a large (N = 289) sample of pediatric epilepsy cases presenting at three tertiary treatment centers. Using confirmatory factor analysis, we found that a model including factors of Attention Span, Learning Efficiency, Free Delayed Recall, Cued Delayed Recall, and Inaccurate Recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The WCST has been used in some models of attention to assess the shifting component of attention (Mirsky et al, 1991(Mirsky et al, , 1999, and in studies of working memory to reflect the preservation of central executive functioning in amnestic disorders (Baddeley & Wilson, 2002;Gooding et al, 2005). Finally, factor analytic studies of the CVLT have confirmed that List A Trial 1 and Trial B load together to form a factor separate from other CVLT scores (Donders, 2008;Griffiths et al, 2006;Wiegner & Donders, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The WCST has been used in some models of attention to assess the shifting component of attention (Mirsky et al, 1991(Mirsky et al, , 1999, and in studies of working memory to reflect the preservation of central executive functioning in amnestic disorders (Baddeley & Wilson, 2002;Gooding et al, 2005). Finally, factor analytic studies of the CVLT have confirmed that List A Trial 1 and Trial B load together to form a factor separate from other CVLT scores (Donders, 2008;Griffiths et al, 2006;Wiegner & Donders, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…After a 20-min delay, participants again recalled List A in free and cued recall manners (long-delay trials) and then had to complete a yes0no recognition test. Based on previous research investigating CVLT-C performance in pediatric clinical populations using Donders' (1999) 5-factor model (Griffiths et al, 2006;Salorio et al, 2005), and Mattson and Roebuck's (2002) analysis of CVLT-C performance in children with PAE, the following CVLT-C variables were analyzed from raw performance scores: trial 1 of List A ("attention span"), trial 5 of List A ("learning efficiency"), total trials of List A ("total learning"), short-delay free and cued recall, long-delay free and cued recall, and delayed recognition.…”
Section: Tests and Measuresmentioning
confidence: 99%
“…Word lists were derived from the California Verbal Learning Test – Children’s Version (CVLT‐C, Delis et al., 1994), which has been shown to have acceptable reliability (coefficient alpha ranging from 0.72 to 0.85; Delis et al., 1994) and construct validity (Griffiths et al., 2006) in children with epilepsy. A 9‐ and 12‐word list was devised for children <9 and ≥9 years of age, respectively.…”
Section: Methodsmentioning
confidence: 99%